Factors associated with severe permanent first molar caries among adolescents from Acapulco, Guerrero. - Juárez-Medel, Carlos Alberto (2022)
Objective: To identify the factors associated with severe caries of the first permanent molar among adolescents from Acapulco, Guerrero, Mexico. Material and methods: Cross-sectional study in a sample of 173 adolescents from first to third grade of a public middle school. A self-administered questionnaire was used to obtain sociodemographic data, socioeconomic level, oral health, toxic and dietary habits. Severe caries was identified based on the combined codes 5-6 of the International Caries Classification and Management System. A multivariate analysis was performed with CIETmap statistical software, which identified factors associated with severe caries with the prevalence ratio and its 95% confidence interval as an estimate of the strength of association. Results: A total of 692 permanent first molars were examined. The 54% of the adolescents (94/173) presented severe caries in at least one molar. Two associated factors were found, consumption of 6 or more cigarettes per day (RPa: 5.48; IC95%a= 2.01 - 17.87), and use of oral hygiene aids (RPa: 0.41; IC95%a= 0.34 - 0.78). Conclusion: The prevalence of severe caries was similar to that reported in other studies. Health promotion actions should be carried out to help reduce caries in this population.